Time in Range and Pregnancy Outcomes in People with Diabetes Using Continuous Glucose Monitoring - Fishel Bartal, Michal; Ashby Cornthwaite, Joycelyn A.; Ghafir, Danna; Ward, Clara; Ortiz, Gladys; Louis, Aleaha; Cornthwaite, John; Chauhan, Suneet S. P.; Sibai, Baha M. (American Journal of Perinatology, 2022)
Objective The international consensus on continuous glucose monitoring (CGM) recommends time in range (TIR) target of >70% for pregnant people. Our aim was to compare outcomes between pregnant people with TIR ≤ versus >70%.Study Design This study was a retrospective study of all people using CGM during pregnancy from January 2017 to May 2021 at a tertiary care center. All people with pregestational diabetes who used CGM and delivered at our center were included in the analysis. Primary neonatal outcome included any of the following: large for gestational age, neonatal intensive care unit (NICU) admission, need for intravenous (IV) glucose, or respiratory distress syndrome (RDS). Maternal outcomes included hypertensive disorders of pregnancy and delivery outcomes. Logistic regression was used to estimate unadjusted and adjusted odds ratios (aORs) with 95% confidence intervals (CIs).Results Of 78 people managed with CGM, 65 (80%) met inclusion criteria. While 33 people (50.1%) had TIR ≤70%, 32 (49.2%) had TIR >70%. People with TIR ≤70% were more likely to be younger, have a lower body mass index, and have type 1 diabetes than those with TIR >70%. After multivariable regression, there was no difference in the composite neonatal outcome between the groups (aOR: 0.56, 95% CI: 0.16–1.92). However, neonates of people with TIR ≤70% were more likely to be admitted to the NICU (p = 0.035), to receive IV glucose (p = 0.005), to have RDS (p = 0.012), and had a longer hospital stay (p = 0.012) compared with people with TIR >70%. Furthermore, people with TIR ≤70% were more likely to develop hypertensive disorders (p = 0.04) than those with TIR >70%.Conclusion In this cohort, the target of TIR >70% was reached in about one out of two people with diabetes using CGM, which correlated with a reduction in neonatal and maternal complications.Key Points
Keywords: neonatal morbidity; hypertensive disorder of pregnancy; continuous glucose monitoring; time in range